UMP MIROS collaboration on road safety technology - Nor Salwana, Mohammad Idris (2020)
Kuala Lumpur, 11 August 2020 - The strategic cooperation opportunity between Universiti Malaysia Pahang (UMP) and the Malaysian Institute of Road Safety Research (MIROS) will benefit both parties in sharing technology, human capital, research and expertise in road safety.